(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
Founding and determination of thermodynamic functions related to solid often geologic materials is traced showing interactions between Czech Professor F. Wald and Russian R.S. Kurnakov and D.S. Korzhinskiĭ in the early definition of phases and characterization of partly open systems. Development of thermodynamic notions regarding solid-state-gas description is reviewed showing its consequence in geology and metallurgy. For the joint definition of the function of mobile components the hyperfree energy was developed and recently put into operation in nonstoichmetric systems. Novel even if unusual term of the associated new variable plutability is explained.